The Comparison of Short- and Long-Term Outcomes for Laparoscopic Versus Open Gastrectomy for Patients With Advanced Gastric Cancer: A Meta-Analysis of Randomized Controlled Trials - Jiang, Jinyan; Ye, Guanxiong; Wang, Jun; Xu, Xiaoya; Zhang, Kai; Wang, Shi (Frontiers in Oncology, 2022)
Objectives The effect of laparoscopic gastrectomy (LG) for the treatment of advanced gastric cancer (AGC) is still controversial. The aim of this meta-analysis was to contrast the short- and long-term outcomes of laparoscopic versus conventional open gastrectomy (OG) for patients with AGC. Methods Databases including PubMed, Embase, Scopus, and Cochrane Library were systematically searched until December 2021 for randomized controlled trial-enrolled patients undergoing LG or OG for the treatment of AGC. Short-term outcomes were overall postoperative complications, anastomotic leakage, number of retrieved lymph node, surgical time, blood loss, length of hospital stay, and short-term mortality. Long-term outcomes were survival rates at 1, 3, and 5 years. Results A total of 12 trials involving 4,101 patients (2,059 in LG group, 2,042 in OG group) were included. No effect on overall postoperative complications (OR 0.84, 95% CI 0.67 to 1.05, p = 0.12, I2 = 34%) and anastomotic leakage (OR 1.26, 95% CI 0.82 to 1.95, p = 0.30, I2 = 0%) was found. Compared with the open approach, patients receiving LG had fewer blood loss (MD -54.38, 95% CI -78.09 to -30.67, p < 0.00001, I2 = 90%) and shorter length of hospital stay (MD -1.25, 95% CI -2.08 to -0.42, p = 0.003, I2 = 86%). However, the LG was associated with a lower number of retrieved lymph nodes (MD -1.02, 95% CI -1.77 to -0.27, p = 0.008, I2 = 0%) and longer surgical time (MD 40.87, 95% CI 20.37 to 54.44, p < 0.00001, I2 = 94%). Furthermore, there were no differences between LG and OG groups in short-term mortality and survival rate at 1, 3, and 5 years. Conclusions LG offers improved short-term outcomes including shorter hospital stays and fewer blood loss, with comparable postoperative complications, short-term mortality, and survival rate at 1, 3, and 5 years when compared to the open approach. Our results support the implementation of LG in patients with AGC. Systematic Review Registration PROSPERO (CRD 42021297141).